Foreign policy vector of Dnipropetrovsk region activities: european values and landmarks - T. A. Bevz, (Ukrainian Cultural Studies, 2018)
The article analyzes the foreign policy vector of Dnipropetrovsk region. The emphasis is put on European values and benchmarks in regional politics. Regions are dynamic socio-systems, which combine past, present and future. The region is an important actor within the political processes that influences the decision-making process in the state. It is noted that Dnipropetrovsk region is a leader in the "level of business development", "infrastructure" and "innovation" segments that promote the European values and landmarks establishment. The European canon of values is not limited by national boundaries, and it is valid beyond our national, ethnic, cultural and religious peculiarities. To some extent, the value changes depend on the characteristics of the regions. However, European values remain the inalienable. In fact, the foundation on which the European Union stands, namely, the headship of law, democracy, freedom of speech, honesty / transparency, the desire to provide equal opportunities for all citizens, and so on. Celebrating Europe Day in the region and holding various events has already started being traditional. Dnipropetrovsk region has become the first member of the Assembly of European Regions in Ukraine, also the first representative office of the Assembly in Ukraine has been opened here. The foreign policy vector of activity in Dnipropetrovsk region is aimed at relations with the European Union and its institutions, and above all, with the Assembly of European Regions. A definite trend in recent decades is concentrated in inter-civilizational dialogues, both at the global and regional levels, by trying to implement individual policies, concluding individual / personalized agreements, treaties, becoming member of international organizations.
Keywords: values, European values, region, "cultural region", Dnipropetrovsk region